PESANTREN DALAM PERUBAHAN SOSIAL - Ismail Ismail (IAIN Pekalongan, 2009)
School of Islamic studies for children and young people (pesantren) is a conventional education institution that â€“ from its publishing until now â€“ it has experienced various changes and played many roles in Indonesia. Its main elements that consist of kyai (the teacher), santri (the student), mosque, boarding school, and kitab kuning (the books) are unique elements that make it different from other education institutions. Along with social change current, there is a view that pesantren is no longer relevant and must be reformed. Therefore, pesantren is demanded to be â€œsupermarketâ€ that supplies many kinds of product and has sensitive curriculum in order to be consumed by its community.